2022
DOI: 10.1002/hsr2.910
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between weight and pulmonary outcomes in overweight and obese people with cystic fibrosis: A retrospective observational study

Abstract: Background A major focus in cystic fibrosis (CF) care aims to increase weight gain. Rates of overweight and obese people with CF have gradually increased over the past decade. Obesity could be a risk for restriction of lung volumes and airway obstruction as well as increase rates of pulmonary exacerbations in people with CF. Aim To assess the relationship between weight categories and pulmonary outcomes in children and adults with CF. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The effect of being overweight or obese on clinical outcomes was also examined. In Italy and New York, a positive correlation between BMI and FEV1pp was seen 91,92 . The association of BMI based on pancreatic status revealed the loss of positive association above the 85th percentile for BMI in PS PwCF, though it continued to increase through the 99th percentile for PI PwCF 70 .…”
Section: Gastrointestinalmentioning
confidence: 94%
See 2 more Smart Citations
“…The effect of being overweight or obese on clinical outcomes was also examined. In Italy and New York, a positive correlation between BMI and FEV1pp was seen 91,92 . The association of BMI based on pancreatic status revealed the loss of positive association above the 85th percentile for BMI in PS PwCF, though it continued to increase through the 99th percentile for PI PwCF 70 .…”
Section: Gastrointestinalmentioning
confidence: 94%
“…The incidence of PwCF who were overweight (BMI 25–29.9 kg/m 2 or 85th to <95th percentile) was reported as 22.1% (71/321) in Italy 19 and 18% in New York, with an overall relative increase in the CFFPR of PwCF categorized as overweight by >300% (8%–17%) 19 . PwCF classified as obese (BMI > 30 kg/m 2 of >95th percentile) was found to be 10% in New York 92 with an overall relative increase by >400% (2%–7%) 19 . All studies revealed individual factors associated with obesity suggesting a milder disease state, 19,90,91 however, the CFFPR found no program‐based factors associated with obesity 19 …”
Section: Gastrointestinalmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, correlation between fat-free mass, BMI and increases in lung function have been noted. This was redemonstrated [27] with a study including both children and adults finding significant direct correlation between BMI and FEV1 in children and adults, at all BMI categories [28]. In contrast the association between BMI and FEV1 was less robust in pancreatic sufficient children, compared to pancreatic insufficient.…”
Section: Pulmonary Functionmentioning
confidence: 98%
“…However, a previous review in adults suggested being overweight/obese was associated with an improved prognosis in pwCF, although there was no extra benefit of having a higher BMI on lung function beyond the range of 28–29 kg/m² 60 . The relationship between overweight and obesity and pulmonary and clinical outcomes has been investigated recently in observational studies 61 and published in a systematic review 62 . The authors concluded that long‐term follow‐up studies are necessary to clarify any adverse effects of having a higher BMI or fat mass (FM) in patients with CF 62 .…”
Section: Introductionmentioning
confidence: 99%